2017
DOI: 10.2147/ijn.s132041
|View full text |Cite
|
Sign up to set email alerts
|

Bioabsorbable self-retaining PLA/nano-sized β-TCP cervical spine interbody fusion cage in goat models: an in vivo study

Abstract: Study design This is an experimental animal study. Objective The objective of this study was to compare an anterior cervical discectomy and interbody fusion of a novel polylactide/nano-sized β-tricalcium phosphate (PLA/nβ-TCP) bioabsorbable self-retaining cervical fusion cage (BCFC) with an autologous bone graft and polyetheretherketone (PEEK) cages. Background Although PLA cervical cages have potential advantages compared with traditional ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 42 publications
1
23
0
Order By: Relevance
“…APC might pose a substantial risk of hardware-related complications, such as plate dislodgement, soft tissue injury, tracheoesophageal lesions, and dysphagia [14,15]. Dysphagia is recognized as the earliest complaint after ACDF using an additional anterior plate.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…APC might pose a substantial risk of hardware-related complications, such as plate dislodgement, soft tissue injury, tracheoesophageal lesions, and dysphagia [14,15]. Dysphagia is recognized as the earliest complaint after ACDF using an additional anterior plate.…”
Section: Discussionmentioning
confidence: 99%
“…Dysphagia is recognized as the earliest complaint after ACDF using an additional anterior plate. The reported incidence of transient dysphagia after ACDF ranges from 2%–71%, and that of chronic dysphagia ranges from 3%–21% [14,16-18]. Studies have found that LSC has a lower risk of dysphagia as a complication, compared with APC, in postoperative and follow-up periods [4].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The reduced stiffness of the poly- l -lactic acid cages demonstrated enhanced interbody fusion compared to the titanium cages at six months. A tri-calcium phosphate cage, autologous bone graft, and polyether ether ketone cage were compared using an in vivo goat model and demonstrated that both cages outperformed the bone graft, with the tri-calcium phosphate device providing the greatest increase in intervertebral bone volume [117]. 3D printed titanium cages have also been tested in vivo and demonstrated good biocompatibility and osseointegration with similar performance to polyether ether ketone materials [30], thus demonstrating the potential in using 3D printing to reach new capabilities in spinal fusion treatments.…”
Section: Clinical Applicationsmentioning
confidence: 99%